Development of Teaching Methods Using Infographic Media and Comic Life Practice Towards Students Learning Interests - Mansyur; Rudi, Ahmad; Iskandar, Akbar (Ceddi Journal of Education, 2022)
The purpose of this study was to develop teaching methods that utilize infographics and Comic Life media to enhance students' interest in learning chemistry. These methods were found to be valid, practical, and effective for use in schools. The research is developmental in nature, employing data analysis techniques to validate the effectiveness and practicality of the developed media. The development process included a needs analysis, design phase, realization/construction phase, testing and evaluation, and implementation. The study's results led to the creation of infographic and Comic Life-based teaching methods that can be seamlessly integrated by teachers and students into the learning process. Instrument validation by experts involved several revisions, ensuring the final media were valid, effective, and practical for classroom use. The validation results showed an average validity score of 4.0. The practicality of these methods was confirmed by their ability to simplify the teaching process for educators and students alike. The methods' effectiveness was evidenced by positive student responses, with 70% strongly agreeing and 30% agreeing with the benefits of the new media. This study contributes to the field of educational methodology by providing innovative tools that merge visual media with traditional teaching, fostering greater student engagement and interest in chemistry. The findings underscore the potential of infographics and Comic Life media to transform how complex subjects are taught, offering new insights for future educational innovations.